2012
DOI: 10.1590/s0365-05962012000100014
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of completion of forms requesting skin biopsies

Abstract: We concluded that information on many of the essential items required for a correct interpretation of the anatomopathologic examination was missing from the request forms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(13 citation statements)
references
References 6 publications
1
11
0
Order By: Relevance
“…Studies from different parts of the world in different laboratory services had shown deficits in filling of laboratory test request forms. [345671011]…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies from different parts of the world in different laboratory services had shown deficits in filling of laboratory test request forms. [345671011]…”
Section: Discussionmentioning
confidence: 99%
“…The previous studies showed that missing information in request form for various laboratory and radiology testing cause delay in treatment process. [34567] Missing information in blood request form leads chances of error and transfusion reactions to the patient. Predetermined transfusion guidelines, pretransfusion approval, and transfusion audits are useful tools in the education of those ordering blood components.…”
Section: Introductionmentioning
confidence: 99%
“…[10,11,20] This study found that the patient demographic data was the best-provided data on the request forms referred for thrombophilia-screen tests, which was in agreement with other studies. [11,12,[19][20][21] The satisfactory completion of demographic data on all the request forms assessed, is largely due to the patient-specific, electronically generated stickers which are mandatory patient identifiers.…”
Section: Discussionmentioning
confidence: 99%
“…A similar previous study indicated that insufficient data on the laboratory request forms influenced the interpretive comment. [ 21 ] In this study, clinical information including the diagnosis or presumptive diagnosis, the presence or absence of acute thrombosis at the time of sample collection, family history of thrombosis, past thrombotic episodes, patient exposure to anticoagulation therapy as well as other medications taken at the time of sample collection such as oral contraceptives, was inadequate on all request forms evaluated. The presence of acute thrombosis decreases PC, PS and AT levels, which can result in a false impression of inherited deficiency.…”
Section: Discussionmentioning
confidence: 99%
“…Nowadays, histopathological examination of specimens is not only an auxiliary means of diagnosis, but also a useful method to assist clinicians with appropriate therapy, proper prognosis prediction, and critical decisions in patient management (1)(2)(3). In the past, the quality of laboratory examinations was determined by the accuracy of the analytical phase (4).…”
Section: Introductionmentioning
confidence: 99%